Unele considerente privind interacțiunea Curții Constituționale cu Parlamentul - Aramă, Elena (CEP USM, 2024)
The Constitutional Court and the Parliament are differents institutions, according to their legal nature, the Parliament being a representative institution with legislative powers and the Constitutional Court – institution for controlling the constitutionality of legal acts. However, their activity intersects with the participation in the legislative process, which does not put the Parliament in a position of subordonation to the Constitutional Court, but of ensuring respect for the Constitution, to which both must obey. The analisis of the jurisprudential practice of the Constitutional Court of the Republic of Moldova demonstrates the courageous position of the Court, which from being a negative legislator (Kelsen), sometimes resorts the position of a positive legislator. The situation exemplified in the case of the exception of unconstitutionality when the Court issues some provisional solutions to protect the rights of people who have a case before a court. The Parliament informed through the Addresses about these provisional solutions and the need to make changes in the normative acts containing the contested provisions.

Curtea Constituțională și Parlamentul sunt organe diferite după natura lor juridică, Parlamentul fiind organ reprezentativ cu atribuții legislative, iar Curtea Constituțională – un organ de control al constituționalității actelor juridice. Totuși, activitatea lor se intersectează prin participarea Curții Constituționale la procesul de legiferare, ceea ce nu pune Parlamentul în poziție de subordonare față de Curtea Constituțională, ci de asigurare a respectului față de Constituție, cărora, ambele organe trebuie să i se supună. Analiza practicii jurisprudențiale a Curții Constituționale a Republicii Moldova demonstrează poziția curajoasă a Curții, care din legiuitor negativ (Kelsen) recurge câte odată la poziția de legiuitor pozitiv. Această situație se exemplifică în cazul excepției de neconstituționalitate, când Curtea emite unele soluții provizorii pentru a proteja drepturile persoanelor ce au un dosar pe rolul unei instanțe judecătorești. Parlamentul este înștiințat prin intermediul adreselor despre aceste soluții provizorii și necesitatea de a face modificări în actele normative ce conțin prevederile contestate.
SOME CONSIFERATIONS REGARDING INTERACTION OF THE CONSTITUTIONAL COURT WITH THE PARLIAMENT
Keywords: Democracy; the rule of law; control of the constitutionallity of laws; the exception of a unconstitutionallity; Addresses sent to the Parliament; democrație; statul de drept; Controlul constituționalității legilor; excepția de neconstituționalitate; adrese trimise Parlamentului